Pendidikan dan Pelatihan Komputer dalam Peningkatan Kualitas Guru di Kecamatan Sukasari Sumedang - Ani Amaliyah; Asep Wasid (LPPM UNINUS, 2016)
In line with the development of information and communication technology (ICT) can not be separated from the availability of facilities and infrastructure and its utilization. The importance of knowledge and insights on ICT and how to get resources is an obligation of the user to improve the quality of knowledge of the importance of ICT. To improve the ability of these technologies will then need to do their training. Inability and limitations to have facilities in information and communication technology, ignorance on the use of computers and the need for self improvement of the users are behind the implementation of this program community service. The aim is to provide information on the importance of ICT, and providing training in the form of computer practice. The method is to do a survey, data collection, data analysis, planning, implementation, assessment and reporting. The result is a program participant gets to know about ICT, as well as getting computer training practices. The implication is that program participants gain knowledge and insight into the use of ICT as well as practices that computer. The conclusion is that education is the process of providing and delivering information and its utilization in theory, training is the practice of theory is given, improving the quality of teachers is the process of adding insight and knowledge, and the use of ICT, so that the program is expected to be a program on improved its quality for teachers in the district SukasariSumedang district